2018
DOI: 10.1016/j.sjbs.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of total flavonoids of raspberry on perimenopausal model in mice

Abstract: To study the effect of raspberry total flavonoids on perimenopausal model in mice. Blank group, sham operation, and the rest of the mice made the menopausal model. Choose 72 mice castrated completely random divided into 6 groups for the experiment, respectively: model group, gengnianan (GNA) capsule group, soybean isoflavone soft (SIS) capsule group, high, mid and low dose group of total flavonoids of raspberry (TFR). Animals in each group were given the corresponding drugs tenth days after operation, and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…90% of estrogen in females is secreted by the ovaries, and the ovariectomy artificially causes a sudden drop in estrogen levels, which then causes menopausal syndrome (Fu et al, 2017). OFT showed that OVX rats have reduced activity and curiosity about the fresh environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…90% of estrogen in females is secreted by the ovaries, and the ovariectomy artificially causes a sudden drop in estrogen levels, which then causes menopausal syndrome (Fu et al, 2017). OFT showed that OVX rats have reduced activity and curiosity about the fresh environment.…”
Section: Discussionmentioning
confidence: 99%
“…The ovariectomized animal model is a classic model with a high success rate and has been widely used in menopause studies, although it is still insufficient for human peri‐menopausal simulations. 90% of estrogen in females is secreted by the ovaries, and the ovariectomy artificially causes a sudden drop in estrogen levels, which then causes menopausal syndrome (Fu et al, 2017). OFT showed that OVX rats have reduced activity and curiosity about the fresh environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of this phenomenon, it is proposed to use kidney-tonifying Yang medicine to treat gynecological diseases. Based on different animal models to confirm the curative effect of kidney-tonifying Yang medicine commonly used in clinical prescription, it has been found that Chinese medicine for kidney-yang has significant effects on perimenopausal syndrome (Fu et al, 2018), perimenopausal depression (Liu et al, 2012), uterine dysplasia and dysmenorrhea. Dodder is a kind of traditional Chinese medicine commonly used for kidney-tonifying, which has many pharmacological effects, such as regulating immunity, anti-aging, protecting liver, regulating reproductive system, protecting cardiovascular and cerebrovascular, lowering blood glucose.…”
Section: Discussmentioning
confidence: 99%
“…Spleens and thymuses of mice were collected and weighed. The spleen and thymus indices were calculated using Equation (2) [19].…”
Section: Measurements Of Spleen and Thymus Indicesmentioning
confidence: 99%